An Overview of Foreign Relation of Nepal with China - Dahal, Girdhari (Journal of Political Science, 2019)
Nepal and China have a long history of foreign relation since ancient time. As a modern state, Nepal established its diplomatic relations with China in 1955. The main objective of this paper is to explore the foreign relation of Nepal with China. This study uses secondary data for the collection of facts and information. It is descriptive and analytical in nature. This study is based on Constitution of Nepal, bilateral treaties, joint statements of high level official visits and different scholarly articles. Basic principles of the foreign policy of Nepal and China is set by mutual trust and the guidelines of Panchasheel. Nepal has always followed and accepted the One-China policy. Also, Nepal has supported the ambitious Chinese initiatives for one belt one road project. Similarly, China has been Nepal's key development partner. China has helped Nepal in different development projects. Nepal has signed a transit treaty with China. Now, Nepal has an alternative for third country transport transit.